Successful patient outcome following surgery of carotid body tumor and temporary hypoglossal nerve dysfunction - Goyal, Vikas Deep (Indian J Thorac Cardiovasc Surg, 2021)
Carotid body tumors, also known as paragangliomas or chemodectomas, are rare tumors. They are mostly benign slow-growing tumors arising from neural crest cells, but can give rise to complications because of their location and close relation to carotid vessels and cranial nerves. A 40-year male patient diagnosed with a carotid body tumor is discussed along with a review of cranial nerve complications associated with the management of carotid body tumors. This case highlights the complete recovery after a temporary hypoglossal nerve deficit following surgery. Another important aspect is that syncopal attacks might occur in carotid body tumors and early surgery is required to prevent complications.